The Relevance of monetary aggregates for monetary policy Purposes in Malaysia - Muzafar Shah, Habibullah; Azali, M.; Puah, Chin Hong; Ahmad Zubaidi, Baharumshah (Institute for Development Studies (Sabah), 2002)
This paper analyses the long-run neutrality (LRN) of money on real output in Malaysia using a reduced form ARIMA model developed by Fisher and Seater (1993). Empirical results are sensitive to the type of data used. Low frequency data are generally more supportive of the neutrality hypothesis. Contrary to Olekalns (1996) and Leong and McAleer (2000), the outcomesof our LRN tests are robust to the measures of money employed.